Tinjauan Yuridis Terhadap Putusan Mahkamah Konstitusi Atas Dugaan Penggunaan Ijazah Palsu Dalam Pemilihan Bupati Kabupaten Pesawaran - Siregar, Tomi Nori Handoko; Irhammudin, Irhammudin (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
This study examines juridically the decision of the Constitutional Court (MK) regarding the alleged use of fake diplomas in the nomination of the Regent of Pesawaran Regency in the 2024 Pilkada. The focus of the study includes the legal basis for the implementation of regional head elections, the authority of the Constitutional Court in resolving disputes, and the legal implications of using invalid documents in the nomination process. Through a normative juridical study approach and analysis of laws and regulations, it is found that the use of fake diplomas is an administrative offense that damages the integrity of the political system and public trust. The Constitutional Court in its decision emphasized the importance of the validity of educational documents as the main requirement for candidacy and rejected candidacies that did not meet these requirements in accordance with the provisions of Law No. 10/2016 and PP No. 3/2024. This study recommends the need for strict document verification, improved regulations, and active community participation to maintain the quality of democracy and fair application of the law in Indonesia.